Isolated mangiferin and naringenin exert antidiabetic effect via PPARγ/GLUT4 dual agonistic action with strong metabolic regulation. (25th January 2018) - Singh, Ashok K.; Raj, Vinit; Keshari, Amit K.; Rai, Amit; Kumar, Pranesh; Rawat, Atul; Maity, Biswanath; Kumar, Dinesh; Prakash, Anand; De, Arnab; Samanta, Amalesh; Bhattacharya, Bolay; et al.
Abstract: In this study, we isolated two compounds from the leaves of Salacia oblonga (SA1, mangiferin and SA2, naringenin), and their structures were confirmed by infrared spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, and mass spectrometry. SA1 and SA2 were orally administered to streptozotocin-induced diabetic rats at 50 and 100 mg/kg daily for 15 days. Blood glucose level, serum lipid profile, oxidative stress parameters, histopathology, docking, molecular parameters, and NMR-based metabolic perturbation studies were performed to investigate the pharmacological activities of SA1 and SA2. Results suggested that both compounds reduced blood glucose level, restored body weight, and normalized lipid concentrations in the serum and oxidative stress biomarkers in the liver and pancreas. In addition, the docking study on several diabetes-associated targets revealed that both compounds had a strong binding affinity towards peroxisome proliferator-activated receptor gamma (PPARγ ) and glucose transporter type 4 (GLUT4). Further real-time reverse transcription polymerase chain reaction and western blot analyses were performed to confirm the gene and protein expression levels of PPARγ and GLUT4 in the pancreatic tissues. Data obtained from the molecular studies showed that both compounds exhibited antidiabetic effects through dual activation of PPARγ /GLUT4 signaling pathways. Finally, the NMR-based metabolic studies showed that both compounds normalized the diabetogenic metabolites in the serum. Altogether, we concluded that SA1 and SA2 might be potential antidiabetic lead compounds for future drug development. Graphical abstract: Highlights: Isolated SA1 and SA2 were screened for antidiabetic property at molecular level. Molecular docking showed their strong binding with PPARγ and GLUT4 targets. Gene and protein expression analysis confirmed their role on PPARγ and GLUT4. Histopathology and SEM showed the restoration of cell architecture after treatments. NMR based metabolomics conformed normalization of altered diabetogenic metabolites.